THE CONTRIBUTION OF BANKING FINANCING TO THE QUALITY OF THE ENVIRONMENT IN INDONESIA - Raodah; Reni Furwanti; Harnisah; Siti Lutpiah Ainun (Institut Agama Islam Negeri (IAIN) Bone, 2025)
The issue behind this research is the increase in temperature due to human activities supported by productive and consumptive financing by banks in Indonesia. This study seeks to ascertain how productive and consumptive financing by banks relates to the environmental quality index in Indonesia. Using a quantitative approach, this study utilizes secondary data. The data was obtained from the official websites of the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and the Ministry of Environment and Forestry (KLHK).Productive Financing Credit (KPP) and Consumptive Financing (KPK) have a significant effect on the Environmental Quality Index (IKLH) both partially and simultaneously. Productive financing affects environmental quality, as can be seen from the large amount of financing involved. For example, purchasing vehicles as a means of product distribution, where the use of these vehicles is frequent, contributes to environmental pollution. Consumptive financing, such as credit for purchasing goods like gadgets, vehicles, or furniture, can negatively reduce the IKLH. For example, consumptive financing makes it easier for people to obtain goods, thereby increasing overall demand. This triggers massive production that requires the extraction of more natural resources such as wood, minerals, and petroleum. The results of the study conclude that productive financing has a significant impact on the IKLH, while consumptive financing has an effect but is not significant on the IKLH. This study is limited to banking financing, so further research can explore in depth the elements that contribute to the Environmental Quality Index outside of banking financing. Future researchers can review in more depth how the production process and use of vehicles affect environmental quality.